Faktor-Faktor Yang Mempengaruhi Tingkat Sustainability Report Dalam Pengungkapan Informasi Laporan Perusahaan Yang Terdaftar Di Jakarta Islamic Indeks - Wahid Wachyu Adi Winarto; M. Arif Kurniawan; Fitri Arini (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2022)
This study aims to examine the factors that can affect the level of sustainability reporting on Islamic companies listed on the Jakarta Islamic Index. Sampling using purposive sampling. The number of observations that are of concern to this study are 55 observations from 2017 to 2021. The data were analyzed using linear regression analysis. Empirical test results show that profitability affects the sustainability report, leverage affects the sustainability report, company size affects the sustainability report and firm value affects the sustainability report.